Gas phase carbonyl compounds in ship emissions: Differences between diesel fuel and heavy fuel oil operation. (July 2015) - Reda, Ahmed A.; Schnelle-Kreis, J.; Orasche, J.; Abbaszade, G.; Lintelmann, J.; Arteaga-Salas, J.M.; Stengel, B.; Rabe, R.; Harndorf, H.; Sippula, O.; Streibel, T.; Zimmermann, R.
Abstract: Gas phase emission samples of carbonyl compounds (CCs) were collected from a research ship diesel engine at Rostock University, Germany. The ship engine was operated using two different types of fuels, heavy fuel oil (HFO) and diesel fuel (DF). Sampling of CCs was performed from diluted exhaust using cartridges and impingers. Both sampling methods involved the derivatization of CCs with 2, 4-Dinitrophenylhydrazine (DNPH). The CCs-hydrazone derivatives were analyzed by two analytical techniques: High Performance Liquid Chromatography–Diode Array Detector (HPLC–DAD) and Gas Chromatography–Selective Ion Monitoring–Mass Spectrometry (GC–SIM–MS). Analysis of DNPH cartridges by GC–SIM–MS method has resulted in the identification of 19 CCs in both fuel operations. These CCs include ten aliphatic aldehydes (formaldehyde, acetaldehyde, propanal, isobutanal, butanal, isopentanal, pentanal, hexanal, octanal, nonanal), three unsaturated aldehydes (acrolein, methacrolein, crotonaldehyde), three aromatic aldehyde (benzaldehyde, p -tolualdehyde, m, o -molualdehyde), two ketones (acetone, butanone) and one heterocyclic aldehyde (furfural). In general, all CCs under investigation were detected with higher emission factors in HFO than DF. The total carbonyl emission factor was determined and found to be 6700 and 2300 μg kWh −1 for the operation with HFO and DF respectively. Formaldehyde and acetaldehyde were found to be the dominant carbonyls in the gas phase of ship engine emission. Formaldehyde emissions factor varied from 3870 μg kWh −1 in HFO operation to 1540 μg kWh −1 in DF operation, which is 4–30 times higher than those of other carbonyls. Emission profile contribution of CCs showed also a different pattern between HFO and DF operation. The contribution of formaldehyde was found to be 58% of the emission profile of HFO and about 67% of the emission profile of DF. Acetaldehyde showed opposite behavior with higher contribution of 16% in HFO compared to 11% for DF. Heavier carbonyls (more than two carbon atoms) showed also more contribution in the emission profile of the HFO fuel (26%) than in DF (22%).